The patient-physician relationship: an account of the physician's perspective - Ron Berger; Ben Bulmash; Netanel Drori; Ofir Ben-Assuli; Ram Herstein (BMC, 2020)
Abstract Background The issue of patient-physician relationships in general, and particularly the trust of patients in their primary care physician has gained much interest in academia and with practitioners in recent years. Most research on this important topic, however, focused on how patients view the relationship and not how the physicians see it. This research strives to bridge this gap, with the resolution of leading to an improved appreciation of this multifaceted relationship. Methods A survey of 328 actively practicing physicians from all four health maintenance organizations (HMOs) in Israel resulted in a hierarchical formation of components, indicating both the relative as well as absolute importance of each component in the formation of the patient-physician relationship. The sample conducted was a convenience one. Methodologically, we used two different complementary methods of analysis, with the primary emphasis on the Analytic Hierarchical Processing (AHP), a unique and advanced statistical method. Results The results provide a detailed picture of physicians' attitudes toward the patient-physician relationship. Research indicates that physicians tend to consider the relationship with the patient in a rather pragmatic manner. To date, this attitude was mostly referred to intuitively, without the required rigorous investigation provided by this paper. Specifically, the results indicate that physicians tend to consider the relationship with the patient in a rather pragmatic manner. Namely, while fairness, reliability, devotion, and serviceability received high scores from physicians, social interaction, friendship, familial, as well as appreciation received the lowest scores, indicating low priority for warmth and sociability in the trust relationship from the physician's perspective. The results showed good consistency between the AHP results and the ANOVA comparable analyses. Conclusions In contrast to patients who traditionally stress the importance of interpersonal skills, physicians stress the significance of the technical expertise and knowledge of health providers, emphasizing the role of competence and performance. Physicians evaluate the relationship on the basis of their ability to solve problems through devotion, serviceability, reliability, and trustworthiness and disregard the "softer" interpersonal aspects such as caring, appreciation, and empathy that have been found to be important to their patients. This illustrates a mismatch in the important components of relationship building that can lead to a loss of trust, satisfaction, and repeat purchase. Policy implications We study the impact physicians' incentives have on the tangible relationship and discuss the significance of physician-patient relationship on satisfaction with the health service given. As a result policies leading to a more dynamic role must be given to the patient, who being well informed by the physician, can help in the decision making process. Policy schemes need to be implemented as a way of changing physicians' behavior, forcing them to better construct and utilize this dyadic relationship.